Factors affecting persistent organic pollutant (POP) accumulation in British Columbia grizzly bears (Ursus arctos horribilis) - Christensen, Jennie R (2008)
This thesis characterizes major factors influencing the accumulation of polychlorinated biphenyls (PCBs), organochlorine (OC) pesticides, and polybrominated diphenyl ethers (PBDEs), in grizzly bears. Dietary differences among grizzly bears have significant implications for contaminant concentrations and patterns. While salmon-eating bears were dominated by lipophilic PCBs, OC pesticides, and lower-brominated PBDEs, non-salmon-eating bears were dominated by the more volatile PCBs and OC pesticides and higher-brominated PBDEs (e.g. BDE-209). Overall, the ocean-salmon-bear pathway appeared to preferentially select for those contaminants with an intermediate log Kow ~6.5, with salmon delivering up to 70% of OC pesticides, 85% of PBDEs and 90% of PCBs to grizzly bears. Fat utilization by grizzly bears during hibernation results in significant contaminant concentration increases in residual fat (“concentration effect”). Overall, total PCBs increased by 2.21 times from pre- to post-hibernation, and total PBDEs by 1.58 times. Interestingly, the patterns of the two distinct pre-hibernation grizzly bear feeding ecologies (salmon- and non-salmon-eating) converged during hibernation, suggesting that shared metabolic capacities drive POP patterns during hibernation. Relative to salmon, grizzly bears have extremely low biomagnification factors (BMFs) for PCBs (0.147), compared to other marine mammals. Low BMF values were a result of >90% depuration (loss) of PCBs through contaminant metabolism and excretion. The results suggest that grizzly bears only metabolize PCB congeners with meta- and para- vicinal hydrogen (H) atoms, suggesting that they have active cytochrome (CYP) P450 2B/3A-like metabolic enzymes. However, congeners structurally resistant to metabolic biotransformation, and those with ortho- and meta- vicinal H atoms, were not readily metabolized, but rather were lost through excretion. This was evidenced by a significant relationship between total retention (Rtotal) of those congeners and log Kow, as well as a ...